Managing Work and Cancer Treatment: Experiences Among Hematological Cancer Survivors - Thomson, Maria D. (Cancer, 2018)
PURPOSE: To characterize the employment status of hematological cancer survivors with an informal caregiver, from diagnosis through the first 6 months of treatment. METHODS: Using a mixed methods approach, semi-structured interviews with hematological cancer survivors were conducted within six months of starting cancer treatment. Interviews assessed cancer treatment status, barriers and facilitators of employment, financial and insurance status, and relationship with the primary caregiver. These results are part of a longitudinal study of cancer survivors and informal caregivers. RESULTS: 171 patients were enrolled. Within 6 months of beginning cancer treatments, 35% were no longer employed. Reasons to remain employed included financial need, employee benefits, and a sense of purpose and normalcy. Employer accommodations and supportive colleagues facilitated continued employment. Logistic regression revealed that higher household income, a desire to work, non-physical job tasks and congruent survivor-caregiver communication were associated with greater odds of remaining employed. CONCLUSIONS: Within six months of commencing cancer treatment, most hematological cancer survivors had maintained employment. Because of the limitations imposed by the physical stress of cancer treatments, as well as the need to maintain employment to continue receiving employee benefits to cover such treatments, hematological cancer survivors would likely benefit from employment accommodations that are sensitive to their unique needs.